Analisis Efektivitas Pemberdayaan Ekonomi Umat pada Bank Wakaf Mikro di Pondok Pesantren As’ad Kota Jambi - Umi Himmatul Aliyah; Maulana Yusuf; Sri Rahma (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This research examines how the effectiveness of people's economic empowerment at the Micro Waqf Bank at the As'ad Islamic Boarding School in Jambi City, phenomena that often occur at the Micro Waqf Bank such as "Customers who have poor characteristics", namely the lack of a sense of care and responsibility for customers for their loans or debts, resulting in losses for micro waqf banks.To find out what are the effectiveness of micro waqf bank empowerment at As'ad Islamic Boarding School in Jambi City, to find out what obstacles are in the effectiveness of micro waqf bank empowerment at As'ad Islamic Boarding School in Jambi City, to find out the benefits of the effectiveness of waqf bank empowerment at As'ad Islamic Boarding School. Researchers used a qualitative method with a descriptive approach. In this case, the informants in this study were the Chairperson, Manager, Supervysore, and customers of the As'ad Islamic Boarding School Micro Waqf Bank in Jambi City. In collecting data, the techniques used are observation, interviews, and documentation, The results of this study found that the financing and business assistance carried out by the Micro Waqf Bank of the As'ad Islamic Boarding School, the effectiveness of people's economic empowerment at the micro waqf bank at the As'ad Islamic Boarding School in Jambi City, Presentation The effectiveness of the success of loans used is right on target, it is estimated that 80% is used according to procedures used to open a business and 20% there are still customers who use it for consumptive activities. The obstacles that arise in empowering the people's economy at the micro waqf bank at the As'ad Islamic Boarding School, the obstacles faced regarding the default of installments. customers who are still difficult to attend halmi activities every week. Keywords: Empowerment, People's Economy, Micro Waqf Bank